Genome-wide association study of PR interval in Hispanics/Latinos identifies novel locus at ID2. Issue 11 (10th November 2017) - Seyerle, Amanda A; Lin, Henry J; Gogarten, Stephanie M; Stilp, Adrienne; Méndez Giráldez, Raul; Soliman, Elsayed; Baldassari, Antoine; Graff, Mariaelisa; Heckbert, Susan; Kerr, Kathleen F; Kooperberg, Charles; Rodriguez, Carlos; et al.
Abstract : Objective: PR interval (PR) is a heritable electrocardiographic measure of atrial and atrioventricular nodal conduction. Changes in PR duration may be associated with atrial fibrillation, heart failure and all-cause mortality. Hispanic/Latino populations have high burdens of cardiovascular morbidity and mortality, are highly admixed and represent exceptional opportunities for novel locus identification. However, they remain chronically understudied. We present the first genome-wide association study (GWAS) of PR in 14 756 participants of Hispanic/Latino ancestry from three studies. Methods: Study-specific summary results of the association between 1000 Genomes Phase 1 imputed single-nucleotide polymorphisms (SNPs) and PR assumed an additive genetic model and were adjusted for global ancestry, study centre/region and clinical covariates. Results were combined using fixed-effects, inverse variance weighted meta-analysis. Sequential conditional analyses were used to identify independent signals. Replication of novel loci was performed in populations of Asian, African and European descent. ENCODE and RoadMap data were used to annotate results. Results: We identified a novel genome-wide association (P<5×10 −8 ) with PR at ID2 (rs6730558), which replicated in Asian and European populations (P<0.017). Additionally, we generalised 10 previously identified PR loci to Hispanics/Latinos. Bioinformatics annotation provided evidence for regulatory function in cardiac tissue. Further, for six loci that generalised, the Hispanic/Latino index SNP was genome-wide significant and identical to (or in high linkage disequilibrium with) the previously identified GWAS lead SNP. Conclusions: Our results suggest that genetic determinants of PR are consistent across race/ethnicity, but extending studies to admixed populations can identify novel associations, underscoring the importance of conducting genetic studies in diverse populations.